Substantiation of the invisible: pedagogical documentation as professional development support - Mesquita, Cristina (2022)
This study started from a collaborative work developed with a group of educators, who work in an institution that welcomes children from 0 to 6 years. The educators, after participating in a seminar on documentation and evaluation in early childhood education, showed enthusiasm to learn how to document the children’s voice and experiences. This study analyses the processes of awareness that occurred over a two-year period of action and that revealed how pedagogical documentation can support educators to reconstruct the image they have of children and the reconfiguration of their practices, substantiating the invisible. The staff-based learning and development is conceptualized from an ecological socio-constructivist following the Pedagogy-in-Participation approach. This piece of research assumes that pedagogical documentation is a process that values the children’s voice and enables educators to reflect, favoring the reconstruction of their practices.